2020
DOI: 10.2147/cmar.s224416
|View full text |Cite
|
Sign up to set email alerts
|

<p>Paeonol Inhibits Pancreatic Cancer Cell Migration and Invasion Through the Inhibition of TGF-β1/Smad Signaling and Epithelial-Mesenchymal-Transition</p>

Abstract: These authors contributed equally to this workPurpose: Paeonol, a natural product derived from the root of Cynanchum paniculatum (Bunge) K. Schum and the root of Paeonia suffruticosa Andr. (Ranunculaceae) has attracted extensive attention for its anti-cancer proliferation effect in recent years. The present study examined the role of paeonol in suppressing migration and invasion in pancreatic cancer cells by inhibiting TGF-β1/Smad signaling. Methods: Cell viability was evaluated by MTT and colonial formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The drug impact on the TGF-β1/Smad signaling pathway is important, not only because it can explain at least partially the anti-fibrotic activity of Nag-D but it can contribute also to the anticancer effects. For example, inhibition of the TGF-β1/Smad pathway has been invoked to explain the anticancer effects of different natural products such as paenol and oridonin [ 41 , 42 ]. Therefore, the recently discovered capacity of Nag-D to regulate the fibroblast-to-myofibroblast transition in atherosclerotic mice deserves further attention because the underlying mechanism is similar to that implicated in the epithelial–mesenchymal transition (EMT) which is known to play a major role to increase motility and invasiveness of cancer cells, and thus to promote cancer metastasis.…”
Section: Other Pharmacological Activities Of Nagilactonesmentioning
confidence: 99%
“…The drug impact on the TGF-β1/Smad signaling pathway is important, not only because it can explain at least partially the anti-fibrotic activity of Nag-D but it can contribute also to the anticancer effects. For example, inhibition of the TGF-β1/Smad pathway has been invoked to explain the anticancer effects of different natural products such as paenol and oridonin [ 41 , 42 ]. Therefore, the recently discovered capacity of Nag-D to regulate the fibroblast-to-myofibroblast transition in atherosclerotic mice deserves further attention because the underlying mechanism is similar to that implicated in the epithelial–mesenchymal transition (EMT) which is known to play a major role to increase motility and invasiveness of cancer cells, and thus to promote cancer metastasis.…”
Section: Other Pharmacological Activities Of Nagilactonesmentioning
confidence: 99%
“…Paeonol (2-hydroxy-4-methoxyacetophenone) has been used as an anti-inflammatory agent ( Lou et al, 2017 ; Zhang L. et al, 2019 ; Zong et al, 2018 ; Al-Taher et al, 2020 ), and also has inhibitory effects on a wide range of cancers including pancreatic, ovarian ( Saahene et al, 2018 ; Gao et al, 2019 ; Cheng et al, 2020 ) ,etc. Recent studies revealed that paeonol could enhance the efficacy of chemotherapeutics, reduce cyclooxygenase-2 (COX-2) and regulate EMT by increasing Human Runt-Related Transcription Factor 3 expression in different types of tumors ( Cai et al, 2014 ; Whittle et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…TGFβ and hypoxia have been reported to trigger the process of EMT, suggesting HCK may play an important role in EMT in GBM development [22,23]. EMT, a trans differentiation process converting epithelial cells into motile mesenchymal cells, is involved in the induction of multiple signaling pathways, and leads to cancer progression [24,25]. Previous studies have indicated that EMT is identified as a mechanism resulting in the invasive phenotype of GBM cells [26,27].…”
Section: Discussionmentioning
confidence: 99%